(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The article evaluates significant Indian IT companies' liquidity from 2005 to 2015. The essay starts by describing the investigation's scope, then briefly reviews accounting and liquidity performance literature. Next, it describes the study's aims, data, and methods. After that, it analyzes the results and concludes.